Efficacy and safety of puerarin injection as an adjunctive therapy for chronic heart failure: a systematic review and meta-analysis - Fan, Hesong; Yang, Jingrong; Wang, Huaizhe; Zong, Shuli; Qu, Yiwei; Wang, Kefei; Zhang, Fengyi; Li, Xiao (Frontiers in Pharmacology, 2025)
ObjectivePuerarin injection is used for the treatment of chronic heart failure (CHF). The objective of this study is to investigate the efficacy and safety of puerarin injection as an adjunct therapy for CHF through a meta-analysis and systematic review.MethodsWe conducted a comprehensive literature search across eight databases, including PubMed, Embase, Web of Science, and Cochrane Library, up to 1 March 2025, to identify the required randomized controlled trials (RCTs). Subsequently, we assessed the included studies according to the principles outlined in the Cochrane Handbook and performed a meta-analysis using RevMan 5.4 and Stata 12.0.ResultsA total of 29 RCTs were included, comprising 2,480 patients, with 1,251 in the Puerarin group and 1,229 in the control group. The meta-analysis demonstrated that puerarin injection combined with conventional medication significantly improved cardiac function parameters in chronic heart failure patients compared to pharmacotherapy alone, including left ventricular ejection fraction (MD = 6.22, 95% CI [3.11, 9.33], P < 0.01), cardiac output (MD = 0.45, 95% CI [0.35, 0.55], P < 0.01), and stroke volume (MD = 3.29, 95% CI [2.02, 4.57], P < 0.01), while reducing left ventricular end-diastolic diameter (MD = −0.83, 95% CI [−1.24, −0.42], P < 0.01). The combination therapy demonstrated both a significantly increased total effectiveness rate (RR = 1.26, 95% CI [1.21, 1.31], P < 0.01) and improved hemodynamic parameters, along with favorable modulation of oxidative stress markers evidenced by elevated superoxide dismutase, glutathione peroxidase, and catalase levels concomitant with reduced lipid peroxidation and malondialdehyde concentrations.ConclusionThis meta-analysis suggests that adjunctive puerarin injection with conventional therapy may provide comprehensive benefits for chronic heart failure management, including improved clinical outcomes, enhanced cardiac function, attenuated ventricular remodeling, optimized hemodynamic performance, and reduced oxidative stress, while maintaining a safety profile comparable to conventional therapy. However, due to the suboptimal quality and some degree of heterogeneity in the existing evidence, there is a need for more high-quality studies to provide more reliable evidence for its future clinical application.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022371583.